2019
DOI: 10.1007/s13524-019-00832-z
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism Underlying Change in the Sex Gap in Life Expectancy at Birth: An Extended Decomposition

Abstract: The relationship between differential mortality rates and differences in life expectancy is well understood, but how changing differential rates translate into changing differences in life expectancy has not been fully explained. To elucidate the mechanism involved, this study extends existing decomposition methods. The extended method decomposes change in the sex gap in life expectancy at birth into three components capturing the effects of the sex difference in mortality improvement (ρ-effect), life table de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In other words, the number of females with shorter lifespan, easier to outlive, decreased over time. Indeed, it has been shown that mortality declined at a faster pace for females than males below age 50, especially in the first half of the 20th century 46 47. This finding implies that more efforts are required today than in the past to reduce these inequalities, for a same difference in life expectancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, the number of females with shorter lifespan, easier to outlive, decreased over time. Indeed, it has been shown that mortality declined at a faster pace for females than males below age 50, especially in the first half of the 20th century 46 47. This finding implies that more efforts are required today than in the past to reduce these inequalities, for a same difference in life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, women benefited from reduced maternal mortality and recorded faster mortality decline at older ages. Efforts in reducing lifespan inequalities must thus target diverse factors, causes and ages 13 46 48…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used across different fields, but its variants are insufficiently integrated. Most researchers know only the variants that directly apply to their issues of interest, such as life expectancy [8,16], job discrimination [6,17], and poverty or inequality [18,19]. Yet all these variants can fit into the general taxonomy presented here.…”
Section: Decomposition Basic Typesmentioning
confidence: 99%